Rancang Bangun Aplikasi Frontend Geographic Information System Menggunakan Metode Rad (Rapid Application Development) - Andini, Novita Rizky; Putri, Raissa Amanda; malika, Sela; Siagian, Andika Fadillah (Jurnal Ilmiah Sains dan Teknologi, 2024)
North Sumatra Province has the fourth largest population in Indonesia after the Provinces of West Java, East Java, and Central Java. In 2022, the population of North Sumatra will reach 15,372,437 people. This means that North Sumatra Province has many vehicles, one of which is motorized vehicles. This makes the community do a lot of services related to motor vehicle tax at Samsat Outlets. Ease of information about the locations of Samsat Outlets is also a mandatory need for the community. The use of internet technology to develop geographic information systems is expected to provide convenience for the public in obtaining information on the location of Samsat Outlets. This system utilizes Google Maps to process and visualize the location of Samsat Outlets. The system is designed using the Rapid Application Development software development method. It is hoped that the public will more easily obtain information about the location of Samsat